Eventos extremos de precipitação em Belém-PA: uma história em notícias de jornais - CAMPOS, Thamiris Luisa de Oliveira Brandão (2019)
Socioeconomic impacts of extreme precipitation events in the city of Belem (1 ° 28'S and 48 ° 29'W) was studying during the period 1987 to 2009, through stories told in newspapers. These events were characterized as extreme, through the Decil Technical, considering although precipitation above 24mm with extreme. These events occur in Belém city, are due to three factors: Influence of mesoscale and large scale phenomena, the very energy of the town as it is located in the Equatorial Zone and the lack of infrastructure in it. The consequences of extreme precipitation events are hail, high winds, falling trees, flooding, traffic congestion and lightning. Despite the atmosphere of the city haven’t a representative pressure gradient occur strong winds, which are capable of unroof many homes and centers commercial employees, and cut down trees. The hail and lightning are not very frequent, but were reported by newspapers. The consequence of more frequent and cause more damage to the city are flooding because the channels suffer from the accumulation of trash and lack of drainage, so they clog and overflow, the news show severe damage such as flooding of streets, homes, schools, even killed people. The three districts most affected by flooding are: Cremação, Jurunas and Batista Campos, these neighborhoods are neighbors, then was featured in the lack of infrastructure the city is the predominant factor on the result of extreme precipitation events, intensifying in some years when there is influence of mesoscale and large scale phenomena